Sonographic Features of a Tuberculous Cold Abscess: A Case Report and Literature Review - Amir Alzarrad; Salman Naeem; Serena Rovida (CINQUILL Medical Publishers Inc., 2023)
The use of point of care ultrasound (POCUS) to aid diagnosis of tuberculosis has been investigated in countries where concomitant endemic prevalence of HIV increases the incidence of extrapulmonary tuberculosis (EPTB). In such cases, using a focused assessment with sonography for HIV-associated tuberculosis (FASH) scan has found to be immensely advantageous as a rapid diagnostic tool in low resource settings where other imaging modalities are scarce. The prevalence of EPTB in immunocompetent patients in industrialised countries is growing. Since EPTB can manifest itself in almost any part of the human body, symptomatic patients present with constitutional and non-specific symptoms. In our case, a 44-year-old male presented to the emergency department (ED) with a 3-month history of left-sided chest pain and swelling of the chest wall. Clinical examination revealed a swollen and tender lump above the left first rib. Palpation of the thoracic (T7) vertebral body demonstrated localised pain. POCUS showed a collection of heterogenous material with fluid content and specks of hyperechoic 'ring-like' structures. Further investigations led to the diagnosis of EPTB. The patient was admitted and treated for EPTB where he went on to make a full recovery. This case report highlights the role of integrating POCUS in clinical examination of patients with suspected EPTB, which can expedite its diagnosis and management.